The effect of preheating of work on chatter during end milling of medium carbon steel performed on a Vertical Machining Center (VMC) - Amin, A. K. M. Nurul; Abdelgadir , M. (American Society of Mechanical Engineers (ASME), 2003)
In the present work causes and after effects of chatter have been discussed and attempts have been made to control the occurrence of chatter during end milling operation conducted on a vertical machining center (VMC). Chatter has been treated as a resonance effect and preheating of the incoming work material layers using high frequency induction heating has been tried as a method of controlling chatter. It has been found that preheating results in substantial lowering down of acceleration amplitude of chatter in a wide range of cutting speed. This has facilitated low tool wear intensity, improved machined surface finish and low noise level during machining. Work material properties were practically unaffected due to low preheating temperature.